2010
DOI: 10.1123/ijsnem.20.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mineral Antioxidant Complex on Clinical Safety, Body Water, Lactate Response, and Aerobic Performance in Response to Exhaustive Exercise

Abstract: MAC supplementation had no impact on aerobic exercise performance and lactate response. Increases in TBW and ICW occurred after MAC consumption, but these changes appeared to have minimal physiological impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, studies about the effect of bicarbonate ingestion on metabolic response are often conflicting. A study conduct on horses by Schuback et al in 2002 reported no effect of sodium bicarbonate ingestion on metabolic response and duration of exercise [23]; contrariwise other study reported in athletes, show an improved performance in a way dose-dependent [24][25][26] and probably by increasing buffering capacity [27,28]. Alkalinizing agents, including sodium bicarbonate, have been proposed as ergogenic aids for their potential effect on providing enhanced extracellular buffer capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies about the effect of bicarbonate ingestion on metabolic response are often conflicting. A study conduct on horses by Schuback et al in 2002 reported no effect of sodium bicarbonate ingestion on metabolic response and duration of exercise [23]; contrariwise other study reported in athletes, show an improved performance in a way dose-dependent [24][25][26] and probably by increasing buffering capacity [27,28]. Alkalinizing agents, including sodium bicarbonate, have been proposed as ergogenic aids for their potential effect on providing enhanced extracellular buffer capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, β-carotene has been found to improve physical performance [ 254 ]. Studies have shown that β-carotene supplementation may lead to endurance strength improvement and injury risk prevention [ 3 , 150 ]. Similarly, a meta-analysis of nine studies including participants from both genders, with a total 190,545 candidates, emphasized that β-carotene leads to a significant enhancement in overall performance [ 29 ].…”
Section: Fat-soluble Vitamins (Fsv)mentioning
confidence: 99%